Unidade da consciência na psicologia do ponto de vista empírico de Franz Brentano - Duarte, Gabriel Lemes (2024)
The aim of this research is to study the concept of the unity of consciousness in the context of Franz Brentano's Psychology from an Empirical Standpoint (1874). Firstly, it will be presented how psychology was conceived as a science of psychic phenomena based on experience and inner perception, and how it was understood to have an advantage over the natural sciences due to the character of immediate evidence of inner perception, which was the fundamental source of psychological knowledge. Secondly, it will be shown how this characteristic of immediate evidence was explained on the basis of a previously unexplained thesis, namely the thesis of the unity of consciousness, i.e. the idea that the act and the consciousness of that act form a unity. Thirdly, it will be shown how the conception that the unity of consciousness is something that consists of a multiplicity of parts was contradictory to the traditional concept of the soul as something absolutely simple and identical to itself, explaining, consequently, how important it was for the philosopher to deny the interchangeability of the concepts of unity and simplicity. This path will lead us to an explanation of the historical-philosophical context of the problem of the unity of consciousness, which will allow us to bring an approximation between the Brentanian concept and the Lockean concept of the unity of consciousness based on inner perception, without appealing to some transcendental instance as a condition for this unity